Providers and Patients Caught Between Standardization and Individualization: Individualized Standardization as a Solution; Comment on "(Re) Making the Procrustean Bed? Standardization and Customization as Competing Logics in Healthcare" - Lena Ansmann; Holger Pfaff (Kerman University of Medical Sciences, 2018)
In their 2017 article, Mannion and Exworthy provide a thoughtful and theory-based analysis of two parallel trends in modern healthcare systems and their competing and conflicting logics: standardization and customization. This commentary further discusses the challenge of treatment decision-making in times of evidence-based medicine (EBM), shared decision-making and personalized medicine. From the perspective of systems theory, we propose the concept of individualized standardization as a solution to the problem. According to this concept, standardization is conceptualized as a guiding framework leaving room for individualization in the patient physician interaction. The theoretical background is the concept of context management according to systems theory. Moreover, the comment suggests multidisciplinary teams as a possible solution for the integration of standardization and individualization, using the example of multidisciplinary tumor conferences and highlighting its limitations. The comment also supports the authors' statement of the patient as co-producer and introduces the idea that the competing logics of standardization and individualization are a matter of perspective on macro, meso and micro levels.